A study of some aspects of the poor white problem in South Africa - Lewis, Robert Alexander (Rhodes University, Faculty of Humanities, Department of History, 1979)
The first instance of the poor white problem being dramatically brought to the attention of white South Africa was in 1893 when Rev. Andrew Murray issued an open letter on the subject which resulted in the convening of the first of many Dutch Reformed Church conferences on the problem (Introduction, p. 1).
Keywords: Poor white problem; Afrikaners -- Economic conditions; Poor -- South Africa; South Africa -- Economic conditions; South Africa -- Social conditions